9(2x-1)(2x-1)-8=0

Simple and best practice solution for 9(2x-1)(2x-1)-8=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2x-1)(2x-1)-8=0 equation:


Simplifying
9(2x + -1)(2x + -1) + -8 = 0

Reorder the terms:
9(-1 + 2x)(2x + -1) + -8 = 0

Reorder the terms:
9(-1 + 2x)(-1 + 2x) + -8 = 0

Multiply (-1 + 2x) * (-1 + 2x)
9(-1(-1 + 2x) + 2x * (-1 + 2x)) + -8 = 0
9((-1 * -1 + 2x * -1) + 2x * (-1 + 2x)) + -8 = 0
9((1 + -2x) + 2x * (-1 + 2x)) + -8 = 0
9(1 + -2x + (-1 * 2x + 2x * 2x)) + -8 = 0
9(1 + -2x + (-2x + 4x2)) + -8 = 0

Combine like terms: -2x + -2x = -4x
9(1 + -4x + 4x2) + -8 = 0
(1 * 9 + -4x * 9 + 4x2 * 9) + -8 = 0
(9 + -36x + 36x2) + -8 = 0

Reorder the terms:
9 + -8 + -36x + 36x2 = 0

Combine like terms: 9 + -8 = 1
1 + -36x + 36x2 = 0

Solving
1 + -36x + 36x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
36 the coefficient of the squared term: 

Divide each side by '36'.
0.02777777778 + -1x + x2 = 0

Move the constant term to the right:

Add '-0.02777777778' to each side of the equation.
0.02777777778 + -1x + -0.02777777778 + x2 = 0 + -0.02777777778

Reorder the terms:
0.02777777778 + -0.02777777778 + -1x + x2 = 0 + -0.02777777778

Combine like terms: 0.02777777778 + -0.02777777778 = 0.00000000000
0.00000000000 + -1x + x2 = 0 + -0.02777777778
-1x + x2 = 0 + -0.02777777778

Combine like terms: 0 + -0.02777777778 = -0.02777777778
-1x + x2 = -0.02777777778

The x term is -1x.  Take half its coefficient (-0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
-1x + 0.25 + x2 = -0.02777777778 + 0.25

Reorder the terms:
0.25 + -1x + x2 = -0.02777777778 + 0.25

Combine like terms: -0.02777777778 + 0.25 = 0.22222222222
0.25 + -1x + x2 = 0.22222222222

Factor a perfect square on the left side:
(x + -0.5)(x + -0.5) = 0.22222222222

Calculate the square root of the right side: 0.471404521

Break this problem into two subproblems by setting 
(x + -0.5) equal to 0.471404521 and -0.471404521.

Subproblem 1

x + -0.5 = 0.471404521 Simplifying x + -0.5 = 0.471404521 Reorder the terms: -0.5 + x = 0.471404521 Solving -0.5 + x = 0.471404521 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 0.471404521 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 0.471404521 + 0.5 x = 0.471404521 + 0.5 Combine like terms: 0.471404521 + 0.5 = 0.971404521 x = 0.971404521 Simplifying x = 0.971404521

Subproblem 2

x + -0.5 = -0.471404521 Simplifying x + -0.5 = -0.471404521 Reorder the terms: -0.5 + x = -0.471404521 Solving -0.5 + x = -0.471404521 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -0.471404521 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -0.471404521 + 0.5 x = -0.471404521 + 0.5 Combine like terms: -0.471404521 + 0.5 = 0.028595479 x = 0.028595479 Simplifying x = 0.028595479

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.971404521, 0.028595479}

See similar equations:

| (3x+3)(3x+3)-27=0 | | 1/2n+4=-3/2-18 | | 3x=x+25 | | x^2-6xy+5y^2-x+5y=0 | | (X-3/7)=2/3(3/2x-9/14) | | .07x+x=5000 | | 1.07x=5000 | | 17/7x=1/2 | | 4/7×x=40 | | -6x-y=-2 | | 200x^2=100 | | 7-3(2y+1)=16 | | 1.75x-0.75y=0 | | 5x^2+5x+5=100 | | 5x^2+6x+6=20 | | 4x+15y=31 | | 7x+6y=41 | | 3(0)-9(1/3)=15 | | 6x-5y=41 | | 3(3)-9(3)=15 | | 5x+2y=1.5 | | 4x-2y=-0.1 | | 1/(1-tanx) | | -9a+8a+36=11 | | 8.99x+4.6y-5.75xy=0 | | 8x+5.5y+6.25xy=0 | | 8x+5.5y-6.25xy=0 | | -9+2y=-66 | | -4x+3y=44 | | n!/(n-2)!=132 | | 3x^2+9=2x+1 | | 3600-x/3 |

Equations solver categories